Learning Technology in the Perspective of the Al-Quran and Hadith - Hermanto; Sari, Fatma (Faculty of Education and Teaching Training, Islamic State University of Kiai Haji Achmad Siddiq Jember, 2022)
This study aims to build the concept of learning technology from the perspective of the Qur'an and Hadith. Learning technology has a role in teaching humans by developing and involving several learning resources, which include human resources, natural and environmental resources, opportunity resources, or opportunities to increase the effectiveness and efficiency of educational resources. This study uses a literature or library research method, namely research that prioritizes theoretical and philosophical data processing. This study's data sources are the Qur'an, Hadith, books, journal articles, and other sources that support this research. The results of this study indicate that Islam through the Al-Qur'an and Hadith illustrates that learning to interpret something must involve a wide range of learning resources, such as one in the Al-Qur'an Surah Al-'Alaq verse 1, namely the universe, environment, and science. Knowledge, human resources, and others. This interpretation is in line with the concept of learning technology that provides an effective and efficient role in the learning process by involving several learning resources, including human resources, natural resources, science, and the environment.